Age-related macular degeneration and its associated factors, in Khartoum locality, Sudan - Harun, Saleh Mohammad Sulaiman; Noma, Mounkaila; El Roubi, Zeinab Yahia (Open Science Journal, 2017)
Introduction: Age-Related Macular Degeneration (AMD or ARMD), also known as Macular Degeneration, is an eye disorder that slowly destroys sharp, central vision. The causal factors of ARMD remain a controversy. The proposed study aimed to participate in controversy in focusing on the magnitude of ARMD in tertiary hospital in Khartoum state. Methods: A hospital-based retrospective cross sectional study design was implemented in Makkah Eye Complex. Data on ARMD was derived from an electronic data based made available to the researcher. The data in excel format was uploaded in the SPSS version 21. All the 79 cases of ARMD was retained and summarized through descriptive statistics to produce graphics and frequency tables to address the research objectives and chi square test was performed to assess the association between ARMD and gender and age. A decision role was set prior to the test to reject the null hypothesis that there was no association whenever the p value is < 0.05. Results: During the period covered by the study a total of 86,788 patients attended Makkah Eye Complex, 79 patients among those was diagnosed as Age Related Macular Degeneration disease. This represents a prevalence of Age Related Macular Degeneration (ARMD) of 0.09 % (79/86,788). Discussion: Regarding age, our findings confirmed that the condition is related to aging. It occurred earlier in our research contrary to the commonly reported years of occurrence. However, the limited data available to us indicates the need to establish an electronic patient registry to enable to describe patients sociodemographic characteristics, the disease risk factors and patient management and related outcomes.